Da oben auf dem Berge - Poppel, Hans (Ellermann, 1990)
Five dwarfs climb a mountain to get a dumpling.
Keywords: Bilderbuch; Dwarfs; German language materials; Stories in rhyme; Kinderlyrik; Zwerg; Deutsch